Pendekatan arsitektur perilaku pada desain Sekolah Khusus Kaum Marjinal di Kota Makassar - Kahfi, Ashabul; As, Zulkarnain; Sudarman, Sudarman (Teknosains: Media Informasi Sains dan Teknologi, 2023)
The Special School for Marginalized Communities is a gathering space and activity center in terms of non-regular education, so as to minimize the growth in unemployment and crime in the city. making spaces as places of shelter, learning, sharpening and socialization of marginalized communities. In this study the method used for data collection was using a mixed method with data mining using the behavioral setting method. Behavioral architecture as a design strategy for Special Schools for Marginalized Communities aims to create an environment that is adapted to the human behavior of its users, which emphasizes aspects of physical and psychological comfort.